Analysis of reticulated dome with universal connector - Oleksandr Gilodo; Andrii Arsirii; Yuliia Somina (Acta Polytechnica)
In order to investigate the stress-strain state of a 4 m diameter reticulated dome model, four series of glued wooden rods were prepared for centric and eccentric compression tests. The tests were carried out in the laboratory of the Department of Metal Wood and Plastic Structures. The stresses at the specific points of the elements were determined through the deformations using the strain gauges. The feature of the prismatic specimens was the stress concentrators in the bearing areas in the form of holes for the arrangement of universal connectors. These areas were also reinforced with steel sleeves. The general conclusion of the study is the high load bearing capacity of the tested samples. The destruction of the samples occurred in the bearing zone due to wood crushing. The next research tasks will be to optimise the dimensions of the elements and test the dome model. The cross-section of the elements, in addition to providing the load-bearing capacity, is also influenced by the need to obtain certain thermal characteristics of the enclosure, i.e. the dome elements should have dimensions that allow placing a layer of an effective insulation in their plane. A special task is to choose a roofing that can be considered only as a part of the constant load on the load-bearing system or as a continuous shell that unbinds the frame.